High-intensity interval training attenuates the exercise-induced increase in plasma IL-6 in response to acute exercise - Croft, L.; Bartlett, J. D.; MacLaren, D. P. M.; Reilly, T.; Evans, L.; Mattey, D. L.; Nixon, N. B.; Drust, B.; Morton, J. P. (Applied Physiology, Nutrition, and Metabolism, 2009)
This aims of this study were to investigate the effects of carbohydrate availability during endurance training on the plasma interleukin (IL)-6, IL-8, and tumor necrosis factor (TNF)-a response to a subsequent acute bout of high-intensity interval exercise. Three groups of recreationally active males performed 6 weeks of high-intensity interval running. Groups 1 (LOW+GLU) and 2 (LOW+PLA) trained twice per day, 2 days per week, and consumed a 6.4 % glucose or placebo solution, respectively, before every second training session and at regular intervals throughout exercise. Group 3 (NORM) trained once per day, 4 days per week, and consumed no beverage during training. Each group performed 50 min of high-intensity interval running at the same absolute workloads before and after training. Muscle glycogen utilization in the gastrocnemius muscle during acute exercise was reduced (p < 0.05) in all groups following training, although this was not affected by training condition. Plasma IL-6 concentration increased (p < 0.05) after acute exercise in all groups before and after training. Furthermore, the magnitude of increase was reduced (p < 0.05) following training. This training-induced attenuation in plasma IL-6 increase was similar among groups. Plasma IL-8 concentration increased (p < 0.05) after acute exercise in all groups, although the magnitude of increase was not affected (p > 0.05) by training. Acute exercise did not increase (p > 0.05) plasma TNF-a when undertaken before or after training. Data demonstrate that the exercise-induced increase in plasma IL-6 concentration in response to customary exercise is attenuated by previous exercise training, and that this attenuation appears to occur independent of carbohydrate availability during training.